A reconfigurable dual‐mode bandpass filter based on substrate integrated waveguide. Issue 4 (April 2017) - Zhang, Qiao‐Li; Adhikari, Sulav; Wang, Bing‐Zhong; Wu, Ke
ABSTRACT: A frequency reconfigurable bandpass filter using an electronically tunable dual‐mode Substrate Integrated Waveguide (SIW) resonator is presented. Four lumped capacitors as electric tuning elements are loaded near the regions of strongest electric field of TE102 and TE201 modes. The resonant frequency of these two orthogonal modes is tuned by different capacitance values of four lumped capacitors coupled to the SIW resonator. Measured results show that the proposed filter exhibits a tuning range of about 37% from 3.44 to 5 GHz with the total insertion loss variation of 1.85–5.2 dB. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:934–937, 2017